Analysis of the use of the BNDES card in Brazilian Regions in the period 2004-2014 - de Vieira Sá, Mauro Thury (2020)
The work aims to analyze aspects of the destination of the values contracted from the BNDES card. It is intended to verify the sectoral bias of the operations contracted via BNDES card per unit of the Federation (UF), as well as to analyze the distribution of these resources in the UFs compared to that of the population and other economic variables. Applying the locational quotient (QL), for the year 2004, the states with the largest number of sectors (five or more) with QL> 1 in the southeastern region were São Paulo, Rio de Janeiro Minas Gerais. In the South, Rio Grande do Sul, in the Northeast Bahia. In the Midwest, the Federal District and Mato Grosso. For 2014, in the southeast, the state of São Paulo, Rio de Janeiro, Minas Gerais and Espírito Santo. In the South, Rio Grande do Sul and Santa Catarina. In the Northeast, Alagoas, Sergipe, Bahia, Ceará, Paraíba, Pernambuco and Rio Grande do Norte. In the Midwest, the Federal District, Goiás, Mato Grosso and Mato Grosso do Sul. To the North, Acre, Amapá, Amazonas, Pará and Tocantins. There was, through the Lorenz Curve, a change in the use of the card, which in 2004 was concentrated in the South and Southeast regions, which together with the Midwest, had specialization in sectors, in which all the federative units of these regions also featured. In 2014, all regions showed specialization in a given activity in all their federal units, in addition to the decrease in the representativeness of the Southeast in the use of the card, with the Northeast gaining a larger share in the total value of operations.